Subjects of Modernity Time-space, disciplines, margins - Dube, Saurabh (African Sun Media, 2017)
"Dube ranges widely and globally - from histories of empires and genealogies of disciplines to recent Dalit artwork from India - to explore and carefully delineate a tension he regards as fundamental to the formation of the modern: the modern subject's inevitable entanglement with those subject to modernity. A tour de force, this book offers a critical, timely and powerful sequel to postcolonial and subaltern studies." - Dipesh Chakrabarty, University of Chicago